Determining stability constants of naringenin (4',5,7-trihydroxy flavanone) complexes with aluminium (III) and iron (II) by potentiometric and spectrophotometric methods - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2007)
Naringenin and its metal complexes are used extensively in chemistry, biology and dye industry. In this study, complexes of naringenin with aluminium and iron are examined by spectrophotometric and potentiometric methods. The stability constants of these complexes were determined potentiometrically by using Calvin-Bjerrum and Irving Rossotti methods. The evaluated protonation constants of the naringenin were found: logK(1),= 10.19, logK(2) = 8.31, and logK(3) = 7.06 at the 25 degrees C. Logarithms of the stability constants were found: for Aluminium complex : logK(1)= 15.39 logK(2) = 7.12, and logK(3)= 6.47 and for Iron complex : logK(1)= 10.11, logK(2)= 6.40, and logK(3) = 6.11 at the 25 degrees C. The components of metal-naringenin complexes are given 1:3 (metal: naringenin ratio) both Al(III) and Fe(II) from the results.
Keywords: naringenin; iron; aluminium; stability constant; potentiometry; spectrophotometry; QUERCETIN 3,3',4',5,7-PENTAHYDROXYFLAVONE COMPLEXES; FLAVONOIDS